A Narrative Analysis of Mining Management Policies by Religious Organizations in Enhancing The Resilience of Civil Society Organizations - Mardhika Agestyaning Hermanto; Muhammad Sya’roni Rofii (International Journal Labs, 2026)
This study analyzes the narrative of mine management policies by religious community organizations (CSOs) from the perspective of organizational resilience. The policy regulated through Government Regulation Number 25 of 2024 and Presidential Regulation Number 76 of 2024 is positioned by the government as an effort to equalize economic access and fair distribution of natural resources, but it raises pros and cons that reflect differences in ideological orientation, institutional capacity, and public perception of the role of mass organizations in the extractive sector. This study used a qualitative approach with the Narrative Policy Analysis (NPA) method to identify the main narratives of the government, counter narratives from civil society, and formulate metanarratives as the basis for more adaptive policy development. The results of the study show that the government's narrative focuses on economic justice, empowerment of the people, and the expansion of the role of CSOs as development actors, while the counter-narrative highlights the risk of environmental damage, social conflicts, ethical dilemmas, and the limitations of technical and institutional capacity of CSOs. From the perspective of organizational resilience, this tension indicates the weakness of environmental sensing capabilities and the accumulation of flexible resources that are the foundation of resilience. This research confirms that the involvement of CSOs in the mining sector has the potential to weaken legitimacy and social capital if it is not balanced with credible social and environmental practices. Therefore, the proposed policy strategy emphasizes strengthening adaptive capacity, accountability, and the placement of CSOs as moral supervisors in natural resource governance to maintain organizational sustainability and support long-term social resilience.